Telegramas de José Celso Barbosa a Roberto H. Todd - Todd, Roberto H.; Barbosa, José Celso (My University, 1912)
Telegrama relacionados a gestiones de Barbosa y Mateo Fajardo.
Keywords: Fajardo, Mateo, 1863-1933